Physical Education Programmes Improve Sportsman’s Motivation, Attitude, and Self-Efficacy: A Mixed Methods Study in Germany - Pamela Giovannelli; Cristina Bandeira (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Physical education plays a crucial role in the holistic development of students; however, it presents a significant challenge for universities in Germany. In order to achieve this objective, a physical activity programme was developed with the intention of providing individualised assistance to enhance both the quantity and quality of physical education. Additionally, the programme aims to promote improvements in self-efficacy, attitudes, and motivation towards physical education, which are influential factors in enhancing athletic performance. Hence, this study investigates the impact of physical education on motivation, attitude, and self-efficacy in promoting physical activity among university students in Germany. In order to achieve the objectives of this study, a sample of 250 athletes from German universities was selected using a convenient sampling technique. The data collected from this sample was primarily quantitative in nature. Additionally, qualitative data was obtained by conducting 15 interviews. The researcher utilised a mixed-methods approach. The data was subjected to analysis using the Statistical Package for the Social Sciences (SPSS) software, employing pre-test and post-test phases. The results obtained from both qualitative and quantitative analyses unequivocally emphasise the significant advantages of the physical education programme for all individuals involved. Significantly, the anticipated effects were observed in terms of important outcomes such as the reduction of negative attitudes, the increase in desire for exercise, and the enhancement of opinions regarding physical ability. The study provided additional evidence that supports the effectiveness of personalised physical education interventions. These interventions have the potential to improve students' attitudes, motivation, and self-efficacy towards physical activity in school settings. The study's conclusion included a discussion on the limitations of the research and potential avenues for future investigation.